Intravenous blood pool activity masquerading as gastrointestinal hemorrhage - Scott A. Fleming; Andrew M. Keenan (World Journal of Nuclear Medicine)
Radiolabeled red blood cell (RBC) scintigraphy is a common study to detect and localize gastrointestinal hemorrhage. There are many potential entities that may result in false-positive RBC scintigraphy. Here, we present a case of enlarged feeding vessels of omental carcinomatosis which scintigraphically might be mistaken as intraluminal bowel activity and thus active hemorrhage. This case highlights the importance of reviewing correlative imaging in patients with a large neoplastic burden.